91.3k views
0 votes
Factor the expression completely over the complex numbers.

x^4−625


Factor the expression completely over the complex numbers.

x^4+10x^2+25

User Naufraghi
by
6.2k points

2 Answers

5 votes


x^4-625=(x^2-25)(x^2+25)=(x-5)(x+5)(x-5i)(x+5i)\\\\x^4+10x^2+25=(x^2+5)^2=((x-\sqrt5i)(x+\sqrt5i))^2=(x-\sqrt5i)^2(x+\sqrt5i)^2

User Risadinha
by
6.7k points
4 votes

Answer:

1)
x^4-625=(x+5i)(x-5i)(x+5)(x-5)

2)
x^4+10x^2+25=(x+√(5)i)^2(x-\sqrt5 i)^2

Explanation:

1) Given : Expression
x^4-625

To find : Factor the expression completely over the complex numbers ?

Solution :

We can re-write the expression as,


x^4-625=(x^2)^2-(25)^2

Applying identity,
a^2-b^2 = (a+b)(a-b)


x^4-625=(x^2+25)(x^2-25)


x^4-625=(x^2+25)(x^2-5^2)

Again apply same identity,


x^4-625=(x^2+25)(x+5)(x-5)

The factor of
x^2+25=(x+5i)(x-5i)

Factor form is
x^4-625=(x+5i)(x-5i)(x+5)(x-5)

2) Given : Expression
x^4+10x^2+25

To find : Factor the expression completely over the complex numbers ?

Solution :

Expression
x^4+10x^2+25

Let
x^2=y


y^2+10y+25

To factor we equate it to zero.


y^2+10y+25=0

Apply middle term split,


y^2+5y+5y+25=0


y(y+5)+5(y+5)=0


(y+5)(y+5)=0

Substitute back,


(x^2+5)(x^2+5)=0


(x^2+5)^2=0


x^2+5=0


x^2=-5

Taking root both side,


x=√(-5)


x=\pm √(5)i

So, The factors are
(x+√(5)i)(x-\sqrt5 i)

Factor form is
x^4+10x^2+25=(x+√(5)i)^2(x-\sqrt5 i)^2

User Bergrebell
by
6.7k points